2016
DOI: 10.1128/jb.00679-15
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Function of a Second, Nonclassical Ahp Peroxidase, AhpA, in Oxidative Stress Resistance in Bacillus subtilis

Abstract: Organisms growing aerobically generate reactive oxygen-containing molecules, such as hydrogen peroxide (H 2 O 2 ). These reactive oxygen molecules damage enzymes and DNA and may even cause cell death. In response, Bacillus subtilis produces at least nine potential peroxide-scavenging enzymes, two of which appear to be the primary enzymes responsible for detoxifying peroxides during vegetative growth: a catalase (encoded by katA) and an alkylhydroperoxide reductase (Ahp, encoded by ahpC). AhpC uses two redox-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 69 publications
1
25
1
Order By: Relevance
“…In contrast to that seen for ahpC , we previously found that expression of ahpA is not altered upon mutation of the other peroxide‐scavenging enzymes (Broden et al., ). Furthermore, ahpA is not substantially expressed during exponential phase and does not appear to be required to protect cells from peroxides during vegetative growth (Broden et al., ). Instead, the expression of ahpA is regulated by the transition‐state regulatory protein AbrB (Broden et al., ; Chumsakul et al., , ).…”
Section: Introductioncontrasting
confidence: 69%
See 4 more Smart Citations
“…In contrast to that seen for ahpC , we previously found that expression of ahpA is not altered upon mutation of the other peroxide‐scavenging enzymes (Broden et al., ). Furthermore, ahpA is not substantially expressed during exponential phase and does not appear to be required to protect cells from peroxides during vegetative growth (Broden et al., ). Instead, the expression of ahpA is regulated by the transition‐state regulatory protein AbrB (Broden et al., ; Chumsakul et al., , ).…”
Section: Introductioncontrasting
confidence: 69%
“…Studies in B. subtilis demonstrate that its two primary peroxide scavengers are AhpC and the vegetative catalase KatA; strains lacking both ahpC and katA grow poorly under aerobic conditions (Broden et al., ; Bsat et al., ). Consistent with this, both ahpC and katA are expressed moderately well during exponential growth (Broden et al., ; Bsat et al., ; Faulkner, Ma, Fuangthong, & Helmann, ; Fuangthong, Herbig, Bsat, & Helmann, ). Furthermore, mutation of either ahpC or katA results in the increased expression of other proteins responsible for protecting cells against peroxides (Antelmann et al., ; Bsat et al., ; Chen, Keramati, & Helmann, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations